Joe DiMaggio : the long vigil - Charyn, Jerome (New Haven [Conn.] : Yale University Press, 2011)
Examines the life of the baseball player in a new light, as a man who took his marriage to Marilyn Monroe very seriously long after their divorce, and had trouble finding a new role for himself during his retirement from the sport.
'Our national exaggeration' -- The walloping wop -- Joltin' Joe and the ghost of Lou Gehrig --'C'mon, Joe, talk to me' -- The wounded warrior -- The princess of Yankee Stadium -- Mr. Marilyn Monroe --'Bigger than the Statue of Liberty' -- The greatest living ball player -- The biggest fan of them all -- Finale : an outfielder's sky.
Includes bibliographical references (p. 147-159) and index.
Keywords: DiMaggio, Joe, -- 1914-1999.; Baseball players -- United States -- Biography